Understanding how low-income communities gain access to healthcare services: A qualitative study in São Paulo, Brazil. (December 2019) - Guimarães, Thiago; Lucas, Karen; Timms, Paul
Abstract: Introduction: Accessibility to healthcare is recognised as an important component in the uptake of healthcare. Accessibility gaps may underpin health inequalities and the burden often born by socially disadvantaged groups who experience higher levels of disease and have shorter lives. This study aims to identify, from the perspective of people on low incomes, the determinants of their ease of access to healthcare, and how this impacts upon short- and long-term mobility strategies for activity participation. Methods: The research takes a qualitative approach, guided by a conceptual framework that combines transport disadvantage and social exclusion perspectives with human needs theories. We employed focus groups to gather views and experiences on healthcare accessibility from 114 residents of 12 low-income neighbourhoods in São Paulo (Brazil). Results: Five emergent themes encompass the main barriers to healthcare accessibility, namely: proximity and remoteness, walking safety, public transport services, personal security issues, and quality of healthcare services. Participants explained the difficulties of gaining access to healthcare beyond factors such as location and distance. A range of inter-related, multidimensional factors shapes the accessibility of the poor to healthcare in São Paulo. Even under severe financial and time constraints, people may travel longer to access facilities perceived as adequate to respond to their health needs. Participants' narratives suggest a strong effect of healthcare inadequacies, such as the poor quality of the patient-provider relationship and the long times needed to receive medical care, on mobility strategies. Conclusions: Within policy setting agendas in Brazil, "objective" assessments of people's ability to access healthcare tend to over-emphasise the spatial separation between patients' home locations and the physical location of healthcare services, most notably in terms of travel time or distance. Tackling health inequalities requires planners to design integrated transport and health policies taking into consideration the adequacy and quality of both transport and healthcare services. Highlights: The paper examines healthcare accessibility by poor residents of a Brazilian city. Travel time and distance are not the most critical accessibility deterrents. People usually assess jointly transport and healthcare service qualities. To overcome barriers, people may travel longer, stay at home or buy private care. Improving transport to closest facilities does not necessarily improve well-being.